A reexamination of latitudinal limits of substorm‐produced energetic electron precipitation. Issue 10 (9th October 2013) - Cresswell‐Moorcock, Kathy; Rodger, Craig J.; Kero, Antti; Collier, Andrew B.; Clilverd, Mark A.; Häggström, Ingemar; Pitkänen, Timo
Abstract [1] The primary sources of energetic electron precipitation (EEP) which affect altitudes <100 km (>30 keV) are expected to be from the radiation belts and during substorms. EEP from the radiation belts should be restricted to locations between L = 1.5 and 8, while substorm‐produced EEP is expected to range from L = 4 to 9.5 during quiet geomagnetic conditions. Therefore, one would not expect any significant D region impact due to electron precipitation at geomagnetic latitudes beyond about L = 10. In this study we report on large unexpectedly high‐latitude D region ionization enhancements, detected by an incoherent scatter radar at L ≈ 16, which appear to be caused by electron precipitation from substorms. We go on to reexamine the latitudinal limits of substorm‐produced EEP using data from multiple low‐Earth orbiting spacecraft, and demonstrate that the precipitation stretches many hundreds of kilometers poleward of the previously suggested limits. We find that a typical substorm will produce significant EEP over the International Geomagnetic Reference Field L shell range L = 4.6 ± 0.2–14.5 ± 1.2, peaking at L = 6–7. However, there is significant variability from event to event; in contrast to the median case, the strongest 25% of substorms have significant EEP in the range spanning L = 4.1 ± 0.1–20.7 ± 2.2, while the weakest 25% of substorms have significant EEP in the range spanning L = 5.5 ± 0.1–10.1 ± 0.7. We also examine the occurrence probability of very large substorms, focusing on those events which appear to be able to disable geostationary satellites when they are located near midnight magnetic local time. On average, these large substorms occur approximately one to six times per year, a significant rate, given the potential impact on satellites.